Peran Perempuan Mesir dalam Konstruk Sosial Pascakolonial - Dzulkifli M. Mooduto (Muwazah, 2018)
This study discusses about the resistance of Egyptian women against social inequality that occurred in two different places with different problems, as depicted in the novel Ar-Rihlah Ayyamu Talibah Misriyyah fi Amrika Radwa 'Asyur’s work. The study reveals the forms of social inequality and also explains clearly the forms of resistance by using the post-colonial theory of Spivak and Homi K. Bhabha which is presented descriptively by deconstructing every fact in this fiction work of Ar-Rihlah Ayyamu Talibah Misriyyah fi Amrika. The result of this study indicated that the resistance to social inequality in terms of gender could be done by frontal. In addition, it also could be done by distorting the common view of women in the social construct of patriarchal society by demonstrating the self capacity and capability. As for the resistance to social inequality in terms of racism also be done in two ways: the first is frontal; and the second is in a way of imitation or mimicry about the West. The forms of imitation are displayed innovel Ar-Rihlah Ayyamu Talibah Misriyyah fi Amrika namely: the first is mimicry about the way of dressing; the second is mimicry to taste the food; and the third is mimicry towards a language. The mimicry toward the West that is done by a leader; Radwa apart as a form of equalization himself with the West to be "objectionable", and also becomes a form of banter (Mockery) against the West for being "inappropriate". Thus, the mimicry efforts undertaken Radwa into a form of resistance because impersonation he did not mimic entirely because he was different from the West.